Preserving Balinese dance through hyperreal digital humans: A motion capture and projection mapping approach - Tombak Matahari; Arya Harditya; Aras Darmawan (Deskomvis: Jurnal Ilmiah Desain Komunikasi Visual, Seni Rupa dan Media, 2025)
This research explores how motion capture and projection mapping technologies can be structured to preserve traditional Balinese dance while supporting creative education in higher learning. The project aimed to create a hyperreal digital human that authentically embodies traditional choreography, guided by the Balinese philosophy of Tri Hita Karana, which emphasizes harmony among the divine, humans, and nature. The production pipeline integrated students and professionals across all stages—from ideation and narrative development to technical execution—using an OptiTrack motion capture system, Blender for 3D modeling, and Unreal Engine for real-time rendering. The cleaned motion data was mapped onto a detailed 3D character representing a celestial Balinese dancer. This digital performance was then projection-mapped onto large structures during the Indonesia Bertutur 2024 festival, engaging audiences with a fusion of tradition and digital art. Results show that motion capture can retain the integrity of traditional movements, while projection mapping serves as a powerful medium for public storytelling. The collaborative model also provided students with direct exposure to industry workflows and cultural material. This study concludes that emerging media can meaningfully support cultural preservation and pedagogical innovation when implemented with respect, structure, and collaboration.